BENTUK DAN PERUBAHAN FUNGSI MUSIK KONGKIL DI DESA BUNGKAL KABUPATEN PONOROGO - Rahayuningsih, Bina Kiki; Santoso, Iwan Budi (Institut Seni Indonesia (ISI) Surakarta, 2020)
Kongkil music was created in 1933 by Eyang Toinangun as a means of gathering the people of Bungkal Village as an effort to resist the Dutch invaders. Kongkil music is an ensemble consisting of instruments of kongkil, kedhang, saron, kethuk, kenong, kempul and gong. In the beginning, Kongkil's music brought songs created by its members with the theme of passion-building, because there was no legacy of the old repertoire of the predecessors. There was an innovation in the form of repertoire changes since 1975, namely bringing dolanan gendhing. Around 2000, Kongkil's music was in a vacuum, then it was revived in 2012 with a new repertoire that presented lancaran and langgam gendhing. The research entitled